2018
DOI: 10.1002/ppsc.201800395
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis and Characterization of Doxycycline‐Loaded Gold Nanoparticles: The Golden Doxycycline for Antibacterial Applications

Abstract: Doxycycline (DOXY) is a tetracycline antibiotic with a potent antibacterial activity against a wide variety of bacteria. One potential strategy to enhance the penetration and the antibacterial activity of antibiotics is the use of nanotechnology. In this work, an innovative synthesis of stable PEGylated‐gold nanoparticles (PEG‐AuNPs) loaded with DOXY is reported. As far as it is known, this is the first report on the combination of DOXY with AuNPs as polymeric complex. The obtained nanoparticles are fully char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“… Ultrasound aided synthesis: This involves the ultrasound reduction of Au precursor in the presence of 2-propanol. The stabilizing agents used include citrate, disulphide and several dendrimers [ 68 , 69 , 70 ]; [ 71 ]. Laser ablation synthesis: Better results with accuracy and reproducibility have been obtained through laser ablation method, by virtue of size and shape.…”
Section: Introductionmentioning
confidence: 99%
“… Ultrasound aided synthesis: This involves the ultrasound reduction of Au precursor in the presence of 2-propanol. The stabilizing agents used include citrate, disulphide and several dendrimers [ 68 , 69 , 70 ]; [ 71 ]. Laser ablation synthesis: Better results with accuracy and reproducibility have been obtained through laser ablation method, by virtue of size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Doxycycline is a broad-spectrum drug with its antimicrobial as well as antitumor activities [ 4 , 8 , 10 , 11 ]. PAR-1 is the receptor protein with which doxycycline binds to inhibit the tumor progression [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Doxycycline is a wide-spectrum drug belonging to the tetracycline family of antibiotics, which has been a drug of choice for treatment of several types of bacterial infections [ 4 ]. Protease-activated receptor-1 (PAR-1) is the member of PARs (protease-activated receptors) family that was identified in 1991 by two independent laboratories during the investigation of thrombin signaling pathway in both hamster and human cells.…”
Section: Introductionmentioning
confidence: 99%
“…In another study semisynthetic tetracycline like doxycycline was coated with AuNPs. The result showed that after conjugation susceptibility of the doxycycline was enhanced and has better antibacterial potential against many pathogens (Haddada et al 2018 ). The AuNPs were also used with antiprotozoal and antifungal drugs like fluconazoal, Amphotericin B and nystatin and it was observed that these drugs after conjugation with AuNPs were more bioactive against Acanthamoeba castellanii (Anwar et al 2019 ).…”
Section: Role Of Coated Nanoparticles In Overcoming the Antibacterial Resistancementioning
confidence: 99%